Desenvolvimento e usabilidade de uma plataforma móvel para apoio ao ensino de reumatologia (Research, Society and Development, 2021)
The use of Information and Communication Technologies impacts medical education, favored by the current profile of students, primarily digital natives. Rheumatology is a complex and critical specialty in medical education. Therefore, the present study aims to develop and evaluate an unprecedented mobile platform in rheumatology, named ReumaChristus, to facilitate knowledge and spread the specialty in the university environment. It was a cross-sectional study with a descriptive design and a quantitative analytical approach with 71 undergraduate medical students, and the usability was assessed by the System Usability Scale (SUS). The result was a SUS score of 87.39 and was statistically significant in the Spearman correlation (p